Assessment of the Quality of Life of Patients with Deforming Osteoarthritis in Primary Health Care - Salaeva M.S; Saidkhonova A.M; Parpibaeva D.A; Salimova N.D.; Tursunova M.U; Ergashov N.Sh (Global Scientific Publishing, 2023)
The article devoted to the questions of the improving quality of life in outpatient clinic and characteristic of the most effective methods of therapeutic physical training in patients.
Keywords: improving quality of life; deforming osteoarthritis